Enterprise Risk Management in Detecting and Preventing Fraudulent Financial Statements - Aulia, Ismi Fitri; Putri, Devi Lestari Pramita; Rahmaniyah, Rahmaniyah (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
The occurrence of fraud is a challenge that every business entity will inevitably face. Historical phenomena of fraud scandals, such as those involving Enron and Worldcom, have demonstrated that robust internal control systems alone are insufficient in preventing fraud, particularly fraudulent financial statements. This study aims to explain how Enterprise Risk Management (ERM) plays a role in anticipating the adverse effects of fraudulent financial reporting. The research is based on a library study, with data gathered from literature sources such as books, encyclopedias, scientific journals, newspapers, magazines, and documents. The results of this study indicate that while ERM can effectively prevent and detect fraud, it is not entirely sufficient to prevent fraudulent financial statements. More effective prevention and detection require the presence and proper functioning of the eight components of ERM, which include the internal environment, objective setting, event identification, risk assessment, risk response, control activities, information & communication, and monitoring, within the organization